Prevalence and Characteristics of Liver Cancer Patients in Immanuel Hospital Bandung within January 2013 until December 2014 Period - Permadi, Achmad R.; Ratnawati, Hana; Wargasetia, Teresa L. (Journal of Medicine and Health, 2016)
Liver cancer is the fifth most common cancer in Indonesia. This research is to find out the prevalence and characteristics of liver cancer patients in Immanuel Hospital Bandung within the January 2013 until December 2014 period based on age, gender, clinical symptoms and predilections. This study was a descriptive verificative research with data retrieval of patients medical records that have been diagnosed with liver cancer that were hospitalized in Immanuel Hospital Bandung within January 2013 until December 2014 period. The study showed that the liver cancer patient prevalence in Immanuel Hospital Bandung within the period of January 2013 until December 2014 was 46 people. Characteristics of liver cancer patients in Immanuel Hospital Bandung within January 2013 until December 2014 period showed that the most liver cancer patients were male, compare with female with ratio 4:1, the most common age group of 56-65 years old, the most common clinical symptoms were abdominal pain with or without reffered pain to the right scapular bone and the most common predilection was right lobe of the liver.Â Key words: liver cancer, patients characteristics, prevalenceÂ